LAPAROSCOPIC VS LICHTENSTEIN HERNIA REPAIR:A LOCAL EXPERIENCE: Hernia Repair - Khan, Dr Jahangir Sarwar; Hassan, Zahra Fatimah; ., Jawad Zahir; ., Hamid Hassan (Pakistan Armed Forces Medical Journal, 2013)
Objective: To compare the operative time, the postoperative pain scores, duration of hospital stay and wound infection rates between Lichtenstein and totally extra peritoneal (TEP) laparoscopic hernia repair for direct inguinal hernias.Design: Comparative study.Place and Duration of study: This study was conducted at surgical unit 1, Benazir Bhutto hospital and surgical unit 1, Holy Family hospital, Rawalpindi from 1st July 2007 to 31st December, 2010.Patients and Methods: A total of hundred patients were divided into open and laparoscopy groups and their age, sex, operative times, pain scores, duration of hospital stay and wound infections were compared and analyzed.Results: Mean age was 60.7 (±9.2) years for open group and 59.7 (±9.3) for the laparoscopic group. Time for surgery was 48.9 minutes in open and 49.0 minutes in the laparoscopic group. Pain scores at 2 hours and 24 hours after surgery were significantly less in laparoscopic group as compared to open group. Hospital stay was 39.6 hours in open versus 31.4 hours in the laparoscopic group , which was also significant. There was no case of wound infection in either groups, requiring operative intervention or mesh removal.Conclusion: The laparoscopic approaches to hernia repair have clear advantages, including lesser post operative pain and shorter hospital stays.